“Opening” a New Kind of School: The Story of the Open High School of Utah - Tonks, DeLaina; Weston, Sarah; Wiley, David; Barbour, Michael K. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
The use of online learning at the primary and secondary school level is growing exponentially in the United States. Much of this growth is with full-time online schools, most of which are operated by for-profit companies that use proprietary online course content. In this article we trace the development of, and philosophy behind, a full-time online school that uses open access software and open educational resources for course content. As more nations begin to put in place plans for primary and secondary education in the event of natural disasters (e.g., the Christchurch earthquakes) or pandemics (e.g., avian flu or H1N1), the availability of open online content is of critical importance.